Biological engineering approaches for modulating the pathological microenvironment and promoting axonal regeneration after spinal cord injury - Chen, Xiaohong; Huang, Rong; Yang, Zhe; Zhang, Jun; Yang, Yanling; Gao, Feng; Liu, Minli; Zhang, Shengjun (Frontiers in Neuroscience, 2025)
Functional recovery following spinal cord injury (SCI) presents significant challenges and imposes a substantial burden on society. Current research primarily focuses on minimizing damage and promoting regeneration to enhance functional recovery after SCI. Following SCI, secondary injuries such as mitochondrial dysfunction, vascular rupture, inflammatory responses, and glial scarring occur in the lesion area, forming the pathological microenvironment. These factors expand the extent of damage, exacerbate injury severity, and severely impede axonal regeneration after SCI. Modulating the pathological microenvironment through various interventions may facilitate axonal regeneration and promote functional recovery after SCI. This article reviews the influence and research advancements in axon regeneration concerning mitochondrial dysfunction, inflammatory response, and glial scar formation after SCI. Additionally, it integrates insights from bioengineering to improve the pathological microenvironment, summarizing the progress in axon regeneration research. The review concludes with novel strategies for enhancing axon regeneration, offering fresh perspectives for future investigations.